2019
DOI: 10.1038/s42255-019-0083-2
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage metabolic remodelling in macrophages in response to lipopolysaccharide and interferon-γ stimulation

Abstract: In response to signals associated with infection or tissue damage, macrophages undergo a series of dynamic phenotypic changes. Here we show that during the response to LPS and interferon-γ stimulation, metabolic reprogramming in macrophages is also highly dynamic. Specifically, the TCA cycle undergoes a two-stage remodeling: the early stage is characterized by a transient accumulation of intermediates including succinate and itaconate, while the late stage is marked by the subsidence of these metabolites. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
115
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(136 citation statements)
references
References 66 publications
10
115
0
1
Order By: Relevance
“…The extracellular metabolic environment and the dynamic changes in the intracellular metabolic milieu orchestrated by metabolic reactions modulate the response to immune signals. In peripheral immune cells, the mechanisms by which inflammation affects energy metabolism are now well-established [ 9 , 10 ]. Similarly, in microglia, recent findings indicate that this immune cell type engages with different metabolic pathways depending on the pattern of stimulation [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The extracellular metabolic environment and the dynamic changes in the intracellular metabolic milieu orchestrated by metabolic reactions modulate the response to immune signals. In peripheral immune cells, the mechanisms by which inflammation affects energy metabolism are now well-established [ 9 , 10 ]. Similarly, in microglia, recent findings indicate that this immune cell type engages with different metabolic pathways depending on the pattern of stimulation [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study first confirmed that metabolic autofluorescence imaging can quantify changes in macrophage metabolism and distinguish macrophage subpopulations within intact, living samples. Differences in NAD(P)H and FAD autofluorescence were first observed in 2D cytokine-stimulated macrophages over 72 hours and reflected the expected metabolic shifts for M(IFN-γ) and M(IL4/IL13) macrophages (Fig 2) (43)(44)(45). This result is consistent with previous metabolic flux and metabolite accumulation studies showing increased glycolysis in LPS-or IFN-γ+TNF-α-stimulated (M1-like) macrophages and increased TCA cycle in IL-4-stimulated (M2-like) macrophages, as well as NAD(P)H lifetime studies distinguishing IFN-γ/LPS-treated and IL-4/IL-13 treated mouse bone marrow-derived macrophages (BMDMs) (16).…”
Section: Discussionmentioning
confidence: 64%
“…This analysis also demonstrates the sensitivity of autofluorescence measurements to temporal functional plasticity commonly reported during macrophage polarization. For example, the bimodal populations observed in redox ratio of polarized macrophages may reflect early-and late-phase metabolic reprogramming shown in recent studies to promote initial upregulation of glycolytic or oxidative processes prior to reestablishing a resting metabolic state (43,46). Notably, autofluorescence imaging provides a unique tool to monitor metabolically-distinct cell sub-populations, unlike standard metabolic flux or metabolite production measurements that monitor bulk changes within a pooled population of cells.…”
Section: Discussionmentioning
confidence: 99%
“…To explore this idea, we sought to map protein modifications induced during mammalian cell differentiation. We chose to study the response of mouse RAW264.7 macrophage cells to lipopolysaccharide (LPS), a potent inducer of macrophage activation and differentiation that involves extensive protein and metabolic signaling (Alasoo et al 2015;Kamal et al 2018;Rattigan et al 2018;Seim et al 2019). We treated RAW264.7 cells with LPS using established methods and analyzed the resultant proteomes by two-dimensional nanoscale liquid chromatography and high-resolution mass spectrometry proteomics (Cifani et al 2018).…”
Section: Figure 1: Outline and Parameterization Of Spectral Alignmentmentioning
confidence: 99%